Interfacial catalytic behaviors of atomic thin SnS2 layer in Li-O2 batteries - Meng, Fanbo; Qin, Jiayao; Zhang, Haolin; Xiong, Xingyu; Hu, Renzong (Applied surface science, 2023)
The interfacial catalytic behaviors of atomic thin SnS2 film on promoting ORR and OER processes in rechargeable Li-O2 batteries are investigated via several ex-situ experimental measurements and theoretical calculations. [Display omitted] •The generation of Sn4+/Sn2+ redox couple act as the catalytic active sites in Li-O2 batteries.•Reaction mechanism between intermediate LiO2 and discharge product Li2O2 is proposed.•Interfacial catalytic active crystalline plane in the SnS2 catalyst is discussed.•Detailed interfacial behaviors of SnS2 are investigated via DFT calculations. Li-O2 battery has been considered to be one of the promising energy storage devices due to its extreme large theoretical energy density. However, the severe electrochemical polarization and irreversible decomposition of the discharge product Li2O2 dramatically prevent its widely applications. In this article, a low-cost 2D atomic thin few-layer SnS2 catalysts synthesized via a modified hydrothermal method are employed as the catalyst cathode for the Li-O2 batteries. The catalytic properties of atomic thin SnS2 layer in the Li-O2 batteries are discussed through systematic experiments and theoretical calculations. It is found that the generation of Sn4+/Sn2+ redox couple in the SnS2 catalyst may act as the active catalytic sites on promoting formation/decomposition for the intermediate LiO2 and discharge product Li2O2 throughout the cycling processes. Moreover, it is calculated that the (001) plane for the SnS2 cathode can reduce the adsorption energy barrier and the catalytic reaction energy gaps for the interface electrochemical reaction in the Li-O2 batteries. Our work may not only reveal the catalystic mechanism of SnS2 for promoting ORR/OER processes in Li-O2 batteries, but also pave a way to explore new SnS2-based electrocatalysts for energy conversion and storage in the future.